Abridged Life Tables for Cephalonomia stephanoderis and Prorops nasuta (Hymenoptera: Bethylidae) Parasitoids of Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) Reared on Artificial Diet. Issue 2 (1st March 2018) - Portilla, Maribel; Grodowitz, Michael
Abstract: Biological aspects and demographic parameters of Cephalonomia stephanoderis Betrem (Hymenoptera: Bethylidae) and Prorops nasuta Waterston (Hymenoptera: Bethylidae) parasitoids of the coffee berry borer (CBB), Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) were investigated using diet-reared CBB hosts. Developmental time from eggs to adults, oviposition, and postoviposition period were comparable for both parasitoids. However, P. nasuta had a considerably longer preoviposition and longevity period averaging 17.3 and 63.1 d, respectively. The reproductive rate for C. stephanoderis was 46.1 daughters per female with a mean generation time of 47.4 d, whereas P. nasuta had a reproductive rate of 18.3 daughters per female in a mean time of 58.6 d. Oviposition behavior was also different with C. stephanoderis typically ovipositing on CBB prepupae and pupae, while P. nasuta preferred prepupae and second-instar CBB larvae. An abridged cohort life table for both parasitoids was constructed for growth rates estimations.